Shopping in Another Dimension: What Keeps Customers Coming Back to Mobile AR? - Sharma, Rishi Raj; Singh, Jivanjot; Saini, Vanita (International Review of Management and Marketing, 2026)
Adopting Taylor and Todd’s “decomposed theory of planned behavior” as a theoretical framework, this study examines the key factors influencing users’ intention to use Mobile Augmented Reality applications for shopping activities. A structural equation modeling approach, utilizing the SmartPLS software version 4.0.9.4, was employed to empirically test the research hypotheses. 261 responses were collected through the survey questionnaire. The results of the study indicate that users’ attitudes, social norms, and perceived behavioral control are significant determinants of user intention to continue using mobile augmented reality applications. Furthermore, interactivity, perceived mobility, and trust positively influenced users’ attitudes toward mobile augmented reality applications. The study provides insights into the essential factors affecting users’ intentions to continue using MAR applications for shopping. Drawing from the study’s findings, developers of mobile augmented reality applications should prioritize offering quick and stable interactive platforms for virtual product try-ons. The current research adds to the body of knowledge regarding both the DTPB and MAR. Firstly, the study applies the DTPB framework to understand user continuance intention in the context of mobile augmented reality shopping applications. It extends the application of DTPB to a relatively new technological domain.